SORT1 promote the metastasis and invasion of hepatocellular carcinoma via p38/β-catenin/ZEB1 signaling pathway - Hongjie Chen; Wei Liao; Yuanhui Jiang; Guichan Liao; Xinrui Gao; Siyi Cen; Lili Liu; Jie Peng; Cai Shaohang (Cell Death and Disease)
Abstract Metastasis is the predominant reason for high mortality of hepatocellular carcinoma (HCC) patients. Understanding the molecular mechanisms underlying HCC metastases is critical. Here, we reported that SORT1 functioned as an oncogene by facilitating HCC metastasis. Elevated SORT1 expression was positively correlated with increased tumor number, advanced TNM stage, and vascular invasion. Mechanistically, SORT1 binds to p38 and enhances its stability. Furthermore, p38 phosphorylates GSK-3β at Ser9, which promotes nuclear accumulation of β-catenin, leading to the transcription of ZEB1 and secretion of exosomes. Knockdown of SORT1 and ZEB1 inhibited HCC metastasis, whereas upregulation of ZEB1 restored SORT1 knockdown-induced suppression of HCC metastasis. SORT1 expression was positively correlated with Sterol regulatory element-binding proteins 2 (SREBP2) and ZEB1 expression in human HCC tissues. In light of these results, SORT1 as a potential prognostic biomarker in HCC and targeting WNT/β-catenin signaling pathway, could be an effective therapeutic strategy against HCC metastasis.